Presupposition of repetition speech flavour in Denny Sumargo's podcast with Laura Anna - Widiastuti, Yuanita; Santoso, Anang; Sumadi (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The new phenomenon in linguistic studies makes pragmatics a prestigious study. One of the topics is presupposition. This research discusses the main problem of the construction of repetition speech flavour and the purpose of its use. This research needs to be done as an effort to review the pragmatic point of view that is present in language speech. The purpose of the research is focused on the explanatory analysis of the form of speech taste repetition on presupposition. Furthermore, the researcher conducted an explanation of the relationship between the use of repetition language style and the conception of speech control. The researcher used qualitative approach with content analysis method. The data collection technique is done by listening and note taking. The result shows that Denny Sumargo's speech taste in structural presupposition refers to repetitive language style. The phenomenon can be seen in the utterances that appear. Of the 47 presuppositions spoken, 33 of them are repetitive structural presuppositions. The use of the language style has a strong conceptual relationship with the social attributes of the interlocutor who suffers from paralysis. The purpose is to strengthen, emphasise, and change the mindset of the interlocutor to be able to have strength again in living a life that is inversely proportional to the previous situation.